Examining the association between users creative thinking and field dependence-independence cognitive style through eye movement components - Nisiforou, Efi (My University, 2015)
This eye tracking study investigated the association between individuals' field dependence - independence cognitive style and level of creative thinking based on users' eye movement behaviour while interacting with a set of visual perceptual tasks. Subjects FD-I cognitive style and creativity were measured with the use of the Hidden Figures Test (HFT) and Torrance Test of Creative Thinking (TTCT). The psychometric methods and the eye tracking-derived data were statistically examined demonstrating a relationship between users' cognitive style, creativity attributes and eye gaze behaviour. This research study adds further to the evidence and theory base of Human-computer interaction for applications in the user-centred design and suggests future directions for research.
Keywords: Eye gaze; Eye-tracking; Field dependence-independence; Hidden Figures Test; Torrance Test of Creative Thinking; Visual stimuli